Welfare of Garment Industry Workers in Improving Family Economy in Sukabumi Regency, West Java - Rizki Muhammad Ramdhan; Rena Yuliana; Afdhal Afdhal; Nathalia Debby Makaruku (Universitas 17 Agustus 1945 Semarang, 2023)
This research is motivated by the changing welfare conditions of workers at PT Muara Griya Lestari (MGL) in Sukabumi Regency over time. The changes in the welfare of workers at PT Muara Griya Lestari have had some positive impacts, notably in meeting the household needs of factory workers' families. Furthermore, the changes in workers' welfare can transform their family's lifestyles. This study aims to examine, analyze, and describe the welfare, lifestyle changes, and the influence of welfare on the lifestyle of workers' families at PT Muara Griya Lestari in Sukabumi Regency, West Java. The research method used in this study is qualitative with a descriptive approach. Data collection techniques employed include interviews, observations, questionnaires, and documentary studies. The results of the study indicate that the welfare of workers at PT Muara Griya Lestari, in general, has changed. Two aspects that have experienced noticeable changes are income and household consumption or expenditure, shifting from the moderate category to the high category. This has had an impact on the changes in the lifestyle of factory workers' families, which can be seen in three dimensions: activities, interests, and opinions. However, the changes in the lifestyle of factory workers' families at PT MGL have not reached a consumptive lifestyle and remain within reasonable conditions. Meanwhile, welfare has only a small influence on the changes in the lifestyle of workers' families. Lifestyle changes are influenced by the social and environmental conditions in which the workers reside. Therefore, lifestyle changes are a process that occurs as a result of the interaction between the members of the workers' families and their environment.